Predicting Suicide Attempts for Racial and Ethnic Groups of Patients During Routine Clinical Care. Issue 3 (24th March 2018) - Coleman, Karen J.; Johnson, Eric; Ahmedani, Brian K.; Beck, Arne; Rossom, Rebecca C.; Shortreed, Susan M.; Simon, Greg E.
Abstract : The aim of this study was to examine variation in suicide ideation and its relationship to risk of suicide attempt in the subsequent 90 days by race and ethnicity. Participants were adults who completed the Patient Health Questionnaire depression module (PHQ9) during an outpatient encounter between January 10, 2010, and December 12, 2012 ( N  = 509, 945 patients; N  = 1, 228, 308 completed PHQ9). Data came from the Virtual Data Warehouse from four health care systems in the Mental Health Research Network. The sample was majority female (73.7%), primarily 30–64 years old (60.1%), healthy (64.5% comorbidity index = 0), and over half were non‐Hispanic White (52.9%). Only Asian patients (OR: 1.31; 95% CI: 1.24, 1.39) had higher odds of reporting suicide ideation when compared to non‐Hispanic White people. All racial and ethnic groups had increased risk for suicide attempt with increased frequency of suicide ideation. The PHQ9 item 9 can be used as an indicator of suicide ideation and risk for suicide attempt up to 90 days after the reported ideation in racial and ethnic minority patients during routine clinical care.